Modeling of twin formation, propagation and growth in a Mg single crystal based on crystal plasticity finite element method. (November 2016) - Qiao, H.; Barnett, M.R.; Wu, P.D.
Abstract: A crystal plasticity finite element method (CPFEM) with a stress relaxation effect for twinning in the constitutive description is employed to simulate twin formation, propagation and growth in Mg single crystals subjected to plane-strain compression along the direction perpendicular to the c -axis of its HCP lattice. Tensile twinning dominates the early stage of plastic deformation and numerical results explicitly show the twinning process including twin formation, propagation and growth. After a twin band (or a narrow twin) is formed, a large gradient of effective stress is found across the band front. Also, the resolved shear stress (RSS) on the twin plane along the twin direction is highly non-homogeneous across the band front. It has been demonstrated that softening facilitates the formation of a twin band and work hardening is contributive to the growth of the twin band. In addition, numerical results indicate that softening plays an important role in the propagation of a twin across a grain boundary with a large misorientation. Highlights: A CPFEM with a stress relaxation effect for twinning is proposed. Numerical results explicitly show how a twin propagates in its parent grain. Softening facilitates the formation of a twin band. Work hardening is contributive to the growth of a twin band. Softening plays a vital role in propagation of a twin across a grain boundary.